THE INTEGRATION BETWEEN SYAR’I AND ASTRONOMY TO DETERMINE THE BEGINNING OF HIJRI CALENDAR: An Applied Study of Moon Elongation to Prove the Hilâl Testimony - Nurkhanif, Muhammad; Muttaqin, Azmi; Imron, Ali; Ahmad, Mohd Razlan (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
This article addresses the persistent inconsistency among Indonesian observers regarding the theoretical and practical criteria for determining the beginning of the Hijri month, specifically in the sighting of the hilâl (new crescent moon). While many observers focus primarily on the hilâl’s height above the horizon, they often overlook the critical factor of the elongation angle during observation. This inconsistency is reflected both theoretically and in practice, as evident in the official decisions issued by the Ministry of Religious Affairs of the Republic of Indonesia. Motivated by this issue, the study analyzes data from hilâl sighting testimonies recorded between 1962 and 2021 to critically evaluate the Ministry’s decrees. Employing a qualitative and descriptive research design, the analysis follows Millis and Huberman’s data classification framework combined with a scientific and doctrinal approach to systematically classify the decrees. The study reveals that 45% of the decisions are classified as ithbât maslahî (pragmatic confirmation), while 55% fall under ithbât takâmulî (ideal confirmation). This division underscores the need for a refined theoretical framework to guide the acceptance of hilâl testimonies and reduce the reliance on pragmatic rather than ideal evidence. Consequently, the study proposes the M2P theory, a method designed to improve the selection process of hilâl testimonies by integrating both height and elongation criteria. This theoretical advancement is urgent for ensuring greater consistency and reliability in the Islamic lunar calendar, which holds significant religious and social implications in Indonesia.